2016
DOI: 10.4103/0972-5229.188196
|View full text |Cite
|
Sign up to set email alerts
|

Experiences in end-of-life care in the Intensive Care Unit: A survey of resident physicians

Abstract: Background and Aims:The practice of intensive care includes withholding and withdrawal of care, when appropriate, and the goals of care change around this time to comfort and palliation. We decided to survey the attitudes, training, and skills of intensive care residents in relation to end-of-life (EoL) care. All residents at our institute who has worked for at least a month in an adult Intensive Care Unit were invited to participate.Materials and Methods:After Institutional Ethics Committee approval, a Likert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 14 publications
3
7
0
Order By: Relevance
“…In our study, 67.7% reported having received information on how to "give bad news" to patients and family members, a result that is similar to those observed in another study conducted in India 23 , where the majority of a sample of 120 resident physicians responded that they felt prepared to discuss prognosis and treatment goals with patients and family members. The communication of bad news is one of the most difficult and most frequent tasks in the practice of health professionals.…”
Section: Resultssupporting
confidence: 87%
“…In our study, 67.7% reported having received information on how to "give bad news" to patients and family members, a result that is similar to those observed in another study conducted in India 23 , where the majority of a sample of 120 resident physicians responded that they felt prepared to discuss prognosis and treatment goals with patients and family members. The communication of bad news is one of the most difficult and most frequent tasks in the practice of health professionals.…”
Section: Resultssupporting
confidence: 87%
“…Our results are comparable to those of Chen et al 12 and Mohamed et al 13 in that the respondents expressed a moderate level of comfort in discussing EOLC issues with the families of critically ill patients. In contrast to the findings of Chen et al 12 and Mohamed et al, 13 we found that anesthesia residents expressed more competency and comfort in dealing with EOLC.…”
Section: Discussionsupporting
confidence: 85%
“…This proportion was similar to that of Lech, Destefani and Bonamigo 14 , in which 77.5% of the clinical staff of a university hospital considered their ability to transmit bad news to the patient as good/very good. Another study, conducted in India by Mohamed et al 15 , showed that the majority of a sample of 120 resident physicians feel comfortable discussing prognosis and treatment goals with patients and family members. However, the same research 15 showed that when the communication involved more delicate issues, more than half (75%) of the physicians never participated in meetings with family members.…”
Section: Discussionmentioning
confidence: 99%
“…Another study, conducted in India by Mohamed et al 15 , showed that the majority of a sample of 120 resident physicians feel comfortable discussing prognosis and treatment goals with patients and family members. However, the same research 15 showed that when the communication involved more delicate issues, more than half (75%) of the physicians never participated in meetings with family members. This contradiction was explained by the fact that the research was self-assessing, that is, the doctors could even say that they felt safe to give bad news, but in reality, when the information to be given was more delicate, many of them did not deliver it.…”
Section: Discussionmentioning
confidence: 99%